Life Satisfaction of Adolescents Living in Northern Cyprus / Kıbrıs’ın Kuzeyinde Yaşayan Ergenlerin Yaşam Memnuniyetleri - Özcan, Banu; Kiraz, Aşkın (Journal of History Culture and Art Research, 2017)
Abstract In this research, the life satisfaction of adolescents who live in Northern Cyprus is examined. Demographic variables of adolescents have been taken into consideration while life satisfaction has been determined. The study has been completed in a way of scan pattern in accordance with quantitative method. The reachable universe of this study included the students attending 9, 10, 11, and 12th grade in the province of Kyrenia Northern Cyprus. The samples of research group included 436 students composed of 209 boys (%47,8) and 227 girls (%52,2). The data collection tools used during the research were, Personal Information Form which consists of demographic data and Multidimensional Life Satisfaction Scale. Multidimensional Life Satisfaction Scale consists of friend satisfaction, school satisfaction, environment satisfaction and self satisfaction sub-dimensions. The data has been analyzed with SPSS 20 package program. As a conclusion, within the sub-dimensions of the scale, friend satisfaction sub-dimension level of participants was found to be higher when compared to school, environment and self-satisfaction sub-dimension levels. Additionally, the life satisfaction points of 436 adolescents have shown a meaningful differentiation according to the school type, attended grades and education levels of mother and father. However, there has been no meaningfull differentiation regarding gender, age, number of siblings, the rank of birth, and the working status of mother and father. Öz Bu araştırmada, Kuzey Kıbrıs’ta yaşayan ergenlerin yaşam memnuniyetleri incelenmiştir. Çalışmada ergenlerin yaşam memnuniyetleri belirlenirken bazı demografik değişkenler göz önüne alınmıştır. Çalışma nicel araştırma yöntemine uygun olarak, tarama deseniyle yürütülmüştür. Araştırmanın ulaşılabilir evrenini Kuzey Kıbrıs’ın Girne Kazasında, 2014-2015 eğitim öğretim yılında 9, 10, 11 ve 12. sınıfa devam eden öğrenciler oluşturmaktadır. Araştırmanın örneklem grubu, evren içerisinde yer alan beş lisenin 9, 10, 11, 12. sınıflarına devam eden 209’u erkek (%47,9), 227’si kız (%52,1) olmak üzere toplamda 436 öğrenciden oluşmuştur. Araştırmada veri toplama aracı olarak demografik bilgilerin yer aldığı Kişisel Bilgi Formu ve Çok Boyutlu Öğrenci Yaşam Doyumu Ölçeği kullanılmıştır. Çok Boyutlu Öğrenci Yaşam Doyumu Ölçeği arkadaş doyumu, okul doyumu, çevre doyumu ve benlik doyumu alt boyutlarından oluşmaktadır. Verilerin analizi SPSS 20 paket programı kullanılarak yapılmıştır. Araştırmanın sonucunda 15-19 yaş grubundaki 436 ergenin yaşam doyumlarının en düşük benlik alt boyutunda, en yüksek ise arkadaş alt boyutunda olduğu bulunmuştur. Ayrıca çalışmada okul alt boyutundan alınan yaşam doyumu puanlarının, çevre alt boyutundan alınan yaşam doyumu puanlarından daha yüksek olduğu bulunmuştur. Katılımcıların yaşam doyumu puanlarının okul, sınıf, anne eğitim ve baba eğitim durumuna göre anlamlı bir farklılık gösterdiği bulunmuştur. Fakat cinsiyet, yaş, kardeş sayısı, doğum sırası, anne çalışma ve baba çalışma durumuna göre anlamlı bir farklılık bulunmamıştır.